Dynamic Covalent Identification of an Efficient Heparin Ligand. (10th August 2018) - Corredor, Miriam; Carbajo, Daniel; Domingo, Cecilia; Pérez, Yolanda; Bujons, Jordi; Messeguer, Angel; Alfonso, Ignacio
Abstract: Despite heparin being the most widely used macromolecular drug, the design of small‐molecule ligands to modulate its effects has been hampered by the structural properties of this polyanionic polysaccharide. Now a dynamic covalent selection approach is used to identify a new ligand for heparin, assembled from extremely simple building blocks. The amplified molecule strongly binds to heparin ( K D in the low μm range, ITC) by a combination of electrostatic, hydrogen bonding, and CH–π interactions as shown by NMR and molecular modeling. Moreover, this ligand reverts the inhibitory effect of heparin within an enzymatic cascade reaction related to blood coagulation. This study demonstrates the power of dynamic covalent chemistry for the discovery of new modulators of biologically relevant glycosaminoglycans.